Frequency and Risk Factors of Lipohypertrophy in Insulin Treated Patients with Diabetes: An Experience from a Tertiary Care Center in Multan (Medical Forum Monthly, 2022)
Objective: The present study aimed to evaluate the frequency and risk factors of lipohypertrophy in insulin treated patients in a tertiary care center in Multan.Study Design: cross sectional descriptive studyPlace and Duration of Study: This study was conducted at the Diabetic Outdoor of Nishtar Hospital, Multan between 1st January 2022 to 31st June 2022.Materials and Methods: We included 360 patients, taking insulin for more than one year in our study. The patients were interviewed about insulin injection habits and the injection sites examined according to a preformed questionnaire.Results: We included 360 patients with diabetes mellitus who used insulin for more than one year. The frequency of lipohypertrophy was 43.6%. Mean duration of diabetes and mean duration of insulin use were 14.68±7.62 years and 8.45±6.1 years, respectively. Longer disease duration, longer insulin use, higher doses, use of ice cold insulin and lack of rotation of injection site were the major risk factors of lipohypertrophy.Conclusion: Lipohypertrophy is a common complication of insulin use related largely to improper injection technique. Patient education and frequent examination of the injection site can help prevent lipohypertrophy.